Developing EFL Teachers' Technological Pedagogical Knowledge Through Practices in Virtual Platform - Zhang, Yu (Frontiers in Psychology, 2022)
Currently, advancements in information and communication technology (ICT) and an increased interest in using the Internet for educational purposes have led educators to work in new virtual settings. However, using technology in teaching requires the understanding and information of English educators. Technological Pedagogical Content Knowledge (TPACK) is an educator's knowledge concept regarding integrating technology into education. Also, how educators integrate technology effectively into their classes is a significant issue, as learning environments are influenced by rapid advances in instructional technology. Consistent with this issue, it is critical for teacher development to integrate ICT into educational tasks in the design, application, and assessment of practices in a virtual setting. To this end, the objective of the present review is to consider the role of practice in the virtual platform in developing EFL teachers' TPACK. Ultimately, some implications are presented for the EFL educational stakeholders.